INTELLIGENT MULTI-AGENT INFORMATION SECURITY SYSTEM - Kussul, N.; Shelestov, A.; Sidorenko, A.; Skakun, S.; Pasechnyk, V. (International Journal of Computing, 2014)
It is proposed an agent approach for creation of intelligent intrusion detection system. The system allows detecting known type of attacks and anomalies in user activity and computer system behavior. The system includes different types of intelligent agents. The most important one is user agent based on neural network model of user behavior. Proposed approach is verified by experiments in real intranet of Institute of Physics and Technologies of National Technical University of Ukraine "Kiev Polytechnic Institute.